Hakikat Bahasa Dalam Era Digital dan Dampak Media Sosial Terhadap Penggunaan Bahasa Gaul Pada Remaja: Systematic Literature Review - Ariska, Nesa; Usiono, Usiono (PT. Alahyan Publisher Sukabumi, 2025)
The phenomenon of slang usage among millennial teenagers has become increasingly widespread with the development of communication technology, especially social media. This study aims to describe the characteristics of millennial teenage slang, including its forms, sources, formation patterns, purposes, and contexts of use. This research employs a qualitative descriptive approach by analyzing data in the form of slang utterances obtained from social media platforms such as Facebook, Twitter, and Instagram. Additionally, interviews were conducted with 15 teenagers who actively use slang. The data analysis technique used is content analysis. The results of the study show that millennial teenage slang is dynamic and diverse. Its sources come from various languages, including regional languages, Indonesian, and foreign languages, which then undergo a formation process through abbreviations, word shortening, acronyms, and various other modifications. The use of slang has various purposes, ranging from simple greetings to more complex expressions of feelings such as sarcasm or admiration. The context of its use is also very varied, generally in informal interactions with peers.